The role of noun termination in grammatical gender assignment in Polish: A psycholinguistic study - Długosz, Kamil (Harrassowitz Verlag, 2023)
Previous research has shown that speakers of a variety of languages benefit from formal gender cues, e.g. word ending, when assigning grammatical gender to nouns. However, the extent to which Polish speakers compute gender based on such cues has not yet been examined. Therefore, the goal of this study was to investigate the role of noun termination in gender assignment in Polish on psycholinguistic grounds. The paper reports on a timed Gender Decision Task which was carried out with 24 adult native speakers of Polish. Participants responded significantly faster to gender-transparent than to gender-opaque feminine nouns. However, no effect of noun termination was observed for masculine and neuter nouns. The results provide psycholinguistic evidence that the ending -a constitutes the strongest gender cue that Polish speakers can depend on when assigning gender to nouns, arguably because it is the only noun ending that shows high availability and reliability in parallel.
Keywords: grammatical gender; gender assignment; gender access; gender cues; Polish